2011
DOI: 10.1530/eje-10-0720
|View full text |Cite
|
Sign up to set email alerts
|

Circulating osteoprotegerin and soluble receptor activator of nuclear factor κB ligand in polycystic ovary syndrome: relationships to insulin resistance and endothelial dysfunction

Abstract: Objective: There is plenty of evidence that osteoprotegerin (OPG) is linked to subclinical vascular damage and predicts cardiovascular disease in high-risk populations. Our aim is to investigate the relationships of OPG/free soluble receptor activator of nuclear factor kB ligand (sRANKL) to insulin resistance, brachial artery flow-mediated vasodilation (FMD), and the carotid artery intima-media thickness (CIMT) in polycystic ovary syndrome (PCOS), a disorder characterized by hyperandrogenism, impaired glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 41 publications
2
33
1
1
Order By: Relevance
“…The absence of a significant relationship between OPG and HOMA-IR is in contrast to a number of other studies [10,[13][14][15] which consisted of patients with relatively high levels of IR -including patients with type 2 diabetes [13,14] or a previous history of gestational diabetes [10]. In a group of 106 obese patients (18 with type 2 diabetes), Gannage-Yared et al found a positive association between OPG and HOMA-IR (r =0.295, P < .01) [13].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The absence of a significant relationship between OPG and HOMA-IR is in contrast to a number of other studies [10,[13][14][15] which consisted of patients with relatively high levels of IR -including patients with type 2 diabetes [13,14] or a previous history of gestational diabetes [10]. In a group of 106 obese patients (18 with type 2 diabetes), Gannage-Yared et al found a positive association between OPG and HOMA-IR (r =0.295, P < .01) [13].…”
Section: Discussioncontrasting
confidence: 85%
“…In the group as a whole, there was a weak but statistically significant relationship between OPG and HOMA-IR (r = 0.146, P = .04). Pepene et al found a positive correlation between OPG and HOMA-IR (r =0.311, P = .021) in a group of women of whom three quarters had polycystic ovarian syndrome -a condition strongly associated with IR [15].…”
Section: Discussionmentioning
confidence: 99%
“…Preserved BMD and the hyperinflammatory state in PCOS could be associated with increased OPG levels. Recent studies, however, reported decreased [53,54] or unchanged [55] OPG levels in PCOS patients versus controls. OPG levels were positively associated with vitamin D, BMD and testosterone, but also with I-CTP, a marker of bone resorption [55].…”
Section: Bone Turnover Markers In Pcosmentioning
confidence: 99%
“…OPG levels were positively associated with vitamin D, BMD and testosterone, but also with I-CTP, a marker of bone resorption [55]. In contrast, Pepene and Escobar-Morreale reported inverse associations between OPG, Ferriman-Gallwey score and free testosterone levels in PCOS, but did not measure BMD [54,53]. Intervention studies in hypogonad men [45] and in transsexual women [56] documented significantly increased BMD [45] and increased OPG/RANKL levels [56] after testosterone treatment, thus supporting the positive association between testosterone levels, OPG and BMD.…”
Section: Bone Turnover Markers In Pcosmentioning
confidence: 99%
See 1 more Smart Citation